Socially and environmentally responsible purchasing: Comparing the impacts on buying firm's financial performance, competitiveness and risk. (10th February 2018) - Ferri, Laura Maria; Pedrini, Matteo
Abstract: The paper presents a study that aims to compare the contribution of social and environmental practices along the purchasing process to economic performance, competitiveness, and risk mitigation of the buying firm. The number of studies dealing with the topic has significantly increased in the last few years. The majority of the extant research is focused on the environmental dimension, whereas fewer studies have explored the social dimension or the combination of both factors. The results are mixed, with some scholars supporting the existence of a positive relationship between socially and environmentally oriented purchasing management and financial performance, competitiveness and risk mitigation and others being more cautious. Relying on suggestions from earlier literature, the study presents an analysis of a database made up of 189 international buying companies operating in Italy, and the results have provoked two main observations. Data were collected through a closed-question questionnaire to purchasing managers, which was defined from items and variables identified in the previous literature. On the one hand, the results corroborated the hypotheses of the study, confirming that both dimensions contribute to firm performance. On the other hand, the findings showed that differences do exist and that the positive relationship between social and environmental dimensions and firm performance depends upon the stage into which those criteria are integrated. The integration of social criteria has proven to impact only risk mitigation throughout the purchasing process, whereas the environmental dimension contributes to risk mitigation and competitiveness when included in the supplier selection phase and to economic performance when considered in supplier relationship management. Highlights: Responsible purchasing management is positively related to firm performances. Socially responsible purchasing management contributes to risk mitigation. Environmental issues in purchasing contribute to risk mitigation and competitiveness.